2008
DOI: 10.3233/jad-2008-14210
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Coenzyme Q as an Antioxidant Strategy for Alzheimer's Disease

Abstract: Increasing evidence suggests that Alzheimer's disease (AD) is associated with oxidative damage that is caused in part by mitochondrial dysfunction. Here we investigated the feasibility of modifying Alzheimer pathology with the mitochondrial antioxidant coenzyme Q (CoQ). Exogenous CoQ protected MC65 neuroblastoma cells from amyloid precursor protein C-terminal fragment (APP CTF)-induced neurotoxicity in a concentration dependent manner, with concentrations of 6.25 µM and higher providing near complete protectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 29 publications
1
61
0
2
Order By: Relevance
“…At the same time, the illness is marked by oxidative damage to the brain [43,44]. As this report shows, acetylcholine may facilitate the reduction of UQ to UQH 2 , one of the main mitochondrial antioxidants and a component of novel Alzheimer treatment strategies [44,45]. Although purely speculative at the present point, our results provide with a hypothesis about a possible contribution to the oxidative damage observed in Alzheimer's disease patients.…”
Section: Discussionmentioning
confidence: 40%
“…At the same time, the illness is marked by oxidative damage to the brain [43,44]. As this report shows, acetylcholine may facilitate the reduction of UQ to UQH 2 , one of the main mitochondrial antioxidants and a component of novel Alzheimer treatment strategies [44,45]. Although purely speculative at the present point, our results provide with a hypothesis about a possible contribution to the oxidative damage observed in Alzheimer's disease patients.…”
Section: Discussionmentioning
confidence: 40%
“…We and others have shown that psoriasin is secreted from epithelial cells [9,20]. We hypothesized that psoriasin secreted from mammary epithelial cells may lead to endothelial cell proliferation.…”
Section: Extracellularly Administered Psoriasin Triggers Proliferatiomentioning
confidence: 99%
“…A NBT assay (Sigma-Aldrich, N5514) was performed as previously described [20]. The absorbance was measured at 630 nm using the Mithras LB940 instrument (Berthold Technologies).…”
Section: Nitroblue Tetrazolium (Nbt) Assay For the Detection Of Rosmentioning
confidence: 99%
“…The antioxidants are potential therapeutics by eliminating ROS and exerting neuroprotective effects on neurons in AD properties both in vitro and in vivo [113] ; its administration to transgenic AD mice also dramatically reduces the amyloid plaque burden [114,115] . Although CoQ10 has not been tested in clinic trials, its analog, idebenone, has been assessed in AD patients, and has beneficial effects on memory and attention [116,117] .…”
Section: Antioxidants As a Treatment For Alzheimer's Diseasementioning
confidence: 99%